Welcome to the April 2024 Issue (Vol: 30, No: 2) and Current News of the European Journal of Therapeutics - Balat, Ayşe; Eren, Şevki Hakan; Menzilcioğlu, Mehmet Sait; Bahşi, İlhan; Doğan, İlkay; Kaplan, Davut Sinan; Karadağ, Mehmet; Özçelik, Ayşe Aysima; Sarı, Fatih; Yıldız, Hamit; Akbaba, Murat; Başkonuş, İlyas (European Journal of Therapeutics, 2024)
Dear Colleagues, We have started to reap the rewards of the improvements we have realized within about a year of being appointed to the editorial team. We are happy to see that the number of articles submitted to the Eur J Ther is increasing day by day. Moreover, this situation allows us to be even more selective in article acceptance. Due to many improvements and updates, we can now publish many articles in early view. Moreover, the early view articles of the Eur J Ther are now indexed as “Early Access” by Web of Science without being assigned to the issue [1]. On the occasion of this editorial, we would like to thank once again all the authors, reviewers, editors, and technical team who contributed to the Eur J Ther. We encourage you to submit your valuable work to the Eur J Ther. We hope to continue to bring you good news on future issues. Sincerely yours,